Pantomim di Indonesia: Sebuah Metode Pendidikan - Nur Iswantara (Institut Seni Indonesia Yogyakarta, 2019)
The learning methods of pantomime in Indonesia in the context of national education can be designed to support character education programs scheduled by the government through formal and non-formal education channels. The purpose of this study of pantomime learning methods is to package the way of parenting in the education realm. The method used is a qualitative method and method of action. The findings of the pantomime learning method are in the form of pantomime concepts and presentation techniques that offer new ways and procedures to improve and enhance the professionalism of the ability to educate pantomimes nationally. Thus in the presentation of pantomime learning with sign language, the expression on the face and body of the culprit can be appreciated by every person, community and citizen of Indonesia and other nations.Keywords: pantomime; the professionalism of educators; character education; formal and non-formal education